Davidson y el pragmatismo clásico - Rossi, Paula (2007)
“Davidson and classical pragmatism”. In this paper I wish to trace some connections between Donald Davidson´s work (1917-2003) and two major representatives of the classical pragmatist movement: Charles S. Peirce (18391914) and William James (1842-1910). I will start with a basic characterization of classical pragmatism; then, I shall examine certain conceptions in Peirce’s and James’ pragmatism, in order to establish affinities with Davidsons’ thought. Finally, and bearing in mind the previous connections, I will reflect briefly on the relevance –often unrecognized– of classical pragmatist ideas in the context of contemporary philosophical discussions.